INFLUENCE OF CAPITAL STRUCTURE AND COMPANY SIZE ON THE COMPANY’S GROWTH IN PT. EMPRESS SIAM GROUP - Rahmayani; Salju; Rahmawati; Goso, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
This study aims to examine the relationship and influence of capital structure and company size on company growth within the service sector. The research employs a quantitative methodology, utilizing Partial Least Squares (PLS) regression analysis. The study analyzes secondary data from 2021-2023, focusing on capital, assets, debt, and the number of employees. Respectively, signifying a large effect on company growth. Both Capital Structure and Company Size were found to have a significant positive influence on company growth. The novelty of this study lies in its focused exploration of the service sector, particularly the under-researched area of how capital structure and company size contribute to growth in this sector. The findings provide valuable insights for strategic financial management, offering a robust empirical basis for decision-making in the service industry.